(untitled) (Research, Society and Development, 2021)
In an attempt to give meaning to learning in Science teaching and make it more effective and attractive, teachers must continually rethink and improve their pedagogical practices, adopting didactic instruments that allow the realization and facilitation of learning, with approaches that lead to reflection on the environmental themes, in a contextualized way. Thus, this research aimed to use carnivorous plants as didactic tools in order to awaken the environmental sensitivity of students from two schools in Quirinópolis, Goiás. Therefore, a pedagogical intervention was carried out involving the exposure of some environmental concepts and a practical activity with carnivorous plants. Before and after the execution of the pedagogical intervention, the students answered questionnaires and made drawings, which helped to verify the validity of the didactic method used. We found that the proposed activity enabled them to learn more about carnivorous plants, noting their ecological importance and the close relationship of the diversity of this group with the state of conservation of the environment in which they live, providing opportunities for reflections on our attitudes that directly impact the environment. Before getting to know the plants, the students’ drawings represented them as “humanized” beings, “people-eaters”, with a dangerous character, presenting a risk to humanity. After the practical class, the drawings already illustrated the real morphological characteristics of these vegetables. Given the data, we can infer that the use of carnivorous plants is an attractive practice for the teaching of Science, especially botany, approaching several themes in a contextualized and interdisciplinary way, favoring a non-fragmented learning.